Connecting histories: Jews and their others in early modern Europe - Bregoli, Francesca; Ruderman, Daṿid (Jewish Culture and Contexts, 2019)
Frontmatter -- Contents -- Introduction. Connecting Histories: Jews and Their Others in Early Modern Europe / Bregoli, Francesca -- Part I. Jews and Their Jewish Others -- Chapter 1. Connecting Stories? A Yiddish Folktale and Its Unpopular Hebrew Versions / Voß, Rebekka -- Chapter 2. “The Poor of Your City Come First”: Jewish Ritual and the Itinerant Poor in Early Modern Germany / Kaplan, Debra -- Chapter 3. A Sixteenth-Century Rabbi as a Published Author: The Early Editions of Rabbi Mordecai Jaffe’s Levushim / Sládek, Pavel -- Chapter 4. New Kabbalistic Genres and Their Readers in Early Modern Europe / Gondos, Andrea -- Chapter 5. The “Significant Other/s” and Their/Our Histories Moshe Idel / Idel, Moshe -- Part II. Jews and Their Non-Jewish Others -- Chapter 6. On the Mysteries of the Law: A Conversation Between Pietro Aretino and Rabbi Elijah Menahem Ḥalfan / Lelli, Fabrizio -- Chapter 7. Praising the “Idolater”: A Poem for Christians by Rabbi Leon Modena / Andreatta, Michela -- Chapter 8. Crossing the Name Barrier: Non-Jewish Names in the Memoirs of Glikl bas Leib and in Early Modern Ashkenazic Jewish Culture / Davis, Joseph -- Chapter 9. Pride and Punishment: Christians and Jews on the Meaning of the Jewish Presence in Worms / Raspe, Lucia -- Chapter 10. A Jewish Easter Lamb: Cultural Connection and Its Limits in a 1716 Prague Procession / Greenblatt, Rachel L. -- Chapter 11. Leibush the Lawless and His Border Tavern / Hundert, Gershon David -- Part III. Conversos and Their Others -- Chapter 12. Alone Among the Sages of Sepharad?: Alfonso de Zamora and the Symbolic Capital of Converso Christian Hebraism in Spain After 1492 / Prado Plumed, Jesús de -- Chapter 13. From “Potential” and “Fuzzy” Jews to “Non-Jewish Jews”/“Jewish Non-Jews”: Conversos Living in Iberia and Early Modern Jewry / Stuczynski, Claude B. -- Notes -- List of Contributors -- Index -- Acknowledgments